1967
DOI: 10.1143/ptp.37.353
|View full text |Cite
|
Sign up to set email alerts
|

Compound Levels and the Shell Model

Abstract: 353A formalism of nuclear reactions is presented which clarifies the meaning of applying the usual shell model calculations to the resonance states as well as the bound states. The main point is the introduction of the internal region in the wave function space. An effective Hamiltonian is defined in this subspace, the diagonalization of which gives the energies and the wavefunctions for the resonance states as well as the bound states. As an application of the theory, calculations of the level widths are carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…This may be the reason why the OPE generates contributions that are not obtained from the OGE, while the ρ and ω meson exchanges give rise to contributions already generated by the OGE [28]. Explicit studies on the literature about the double counting problem concluded that while the pion can be safely exchanged together with the gluon, the vector and axial mesons cannot [29]. Finally, any model imitating QCD should incorporate another nonperturbative effect, confinement, that takes into account that the only observed hadrons are color singlets.…”
Section: Su(3) Constituent Quark Modelmentioning
confidence: 99%
“…This may be the reason why the OPE generates contributions that are not obtained from the OGE, while the ρ and ω meson exchanges give rise to contributions already generated by the OGE [28]. Explicit studies on the literature about the double counting problem concluded that while the pion can be safely exchanged together with the gluon, the vector and axial mesons cannot [29]. Finally, any model imitating QCD should incorporate another nonperturbative effect, confinement, that takes into account that the only observed hadrons are color singlets.…”
Section: Su(3) Constituent Quark Modelmentioning
confidence: 99%
“…As an example we mention the non-relativistic constituent quark models, which are very successful in describing the properties of baryons [146]. Based on such constituent quark models, so-called quark cluster models have been developed for the NN interaction [1,147,148]. These models include the effects of one-gluon-exchange terms and account for the exchange of mesons between the quarks.…”
Section: Effects Of Correlations Derived From Realistic Interactions mentioning
confidence: 99%
“…[22] to derive an effective NN interaction from pion-quark exchange. The resulting NN interaction is non-local and gives scattering phase-shifts numerically similar to the ones obtained with the resonating group method [21]. After a long calculation, with the extensive use of the substitution rules of Ref.…”
Section: Exchange and Pionic Contributionsmentioning
confidence: 53%